ChemInform Abstract: Palladium‐Catalyzed Annulation of Internal Alkynes in Aqueous Medium. Issue 38 (10th September 2014) - Ang, Wei Jie; Tai, Chih‐Hsuan; Lo, Lee‐Chiang; Lam, Yulin
Abstract It is demonstrated, that a reusable palladacycle efficiently catalyzes the carbo‐ and heteroannulation of internal alkynes with a wide variety of functionalized aryl halides in aqueous media.